A Genetic Evaluation Of Some Reproductive Traits Of Holstein-Friesian Cattle In Five Syrian Dairies - Omar Mardenli; Mahdi Saleh Mohammad Alkerwi; Hadi Awad Hassooni (ISPEC Journal of Agricultural Sciences)
Many of the reproductive traits in cows are affected by a group of factors, the most important of which are climatic conditions and the management of the herds. In this paper, the reproductive status of imported Holstein - Friesian cattle breed was evaluated in terms of breeding through the investigation for some traits under the influence of some factors. The records involved cow birth to first service trait (CBFS) (1101 records), cow birth to first days open trait (CBFDO) (1091 record), and age at first calving trait (AFC) (1083 record). The results of the study showed significant differences in CBFS, CBFDO, and AFC traits according to the year and season of birth (p <0.01), the lowest values were 19.33, 21.29 and 30.29 months (the year 2000) and 19.40,21.30 and 30.32 months (winter) respectively. Also. a significant difference (p <0.01) was noticed through the interaction between the year and season of birth and between the year of birth and total milk yield level (TMYL). Estimated heritability(h2) for CBFS, CBFDO, and AFC traits were 0.22,0.25 and 0.17 respectively. The study showed variation in estimated breeding values (EBVS) across sires within the reproductive traits. The first three lowest values were achieved by the sires 13,25 and 20, the values were -1.97, -1.87 and -1.86 months (CBFS trait), -2.33, -2.21 and -2.19 months (CBFDO trait), -2.32, -2.20 and -2.18 months (AFC trait) respectively. Based on current given results, it is advised to direct and intensify births during winter and spring seasons to obtain optimal reproductive performance of the herd later.